Age-dependent dose increase during an acute electroconvulsive therapy series - Plemper, Jana; Sartorius, Alexander; Karl, Sebastian (The journal of ECT, 2023)
Introduction - Electroconvulsive therapy (ECT) dose is highly relevant for ECT efficacy as well as adverse effects. It is often based on seizure threshold (ST). Studies have shown that ST increases over the course of an ECT series. Clinical observation suggests that this rise might be more pronounced in geriatric patients. - Methods - Retrospectively, we analyzed ECT dose during the first 20 ECT treatments in 472 patients undergoing ECT. Dose adjustments were assessed in relation to patients' age using generalized least squares regression analysis. Response was defined as Clinical Global Impression Improvement Scale < 4. - Results - Dose increased in all patients during the course of the ECT series (mean initial dose, 64.97 ± 68.04 mC; at 10th ECT, 385.46 ± 211.28 mC). Dose was significantly correlated with ECT treatment number, electrode placement, and the interaction between age and ECT treatment number. In other words, dose increase was significantly positively correlated with increasing age, that is dose increased more in older compared with younger patients during the course of an ECT series (z = 9.47, P < 0.001). Response was not correlated with age-dependent dose increase; however, the length of the ECT series in responders was negatively associated with the dose increase from the first to the seventh ECT session (F = 5.28, P = 0.0228). - Conclusions - Our results indicate that ST increases more rapidly during the course of an ECT series in older compared with younger patients. To ensure high efficacy throughout the course of treatment, attention should be paid to decreasing seizure quality, especially in older patients, and dose should be adjusted accordingly.
Gesehen am 20.11.2023